The effect of boron, copper, and magnesium on the ignition of HEM containing aluminum powder; Journal of Physics: Conference Series; Vol. 1675 : Thermophysics and Physical Hydrodynamics - Sorokin I. V. Ivan Viktorovich (2020, 2020)
Title screen